Getting your first job - Uhl, Xina M.; Harmon, Daniel E. (Uhl, Xina M. Managing your money and finances., 2020)
Teaches readers about the economics involved in getting one's first job. Discusses issues such as preparation, salaries, taxes, schedules, and spending strategies. Includes a glossary, sources for further research, and an index.